The neurological and epigenetic basis of psychosomatic pain: A narrative review. - Vadhavekar, Nidhi; Pandya, Manu; Naveed, Eisha; Gunasekaran , Revan; Muskan,; Mitra, Purbali; Adinew , Biniam; Muhammad Junaid, (Student's Journal of Health Research Africa, 2025)
Psychosomatic disorders, which were once dismissed as "all in the mind," are now understood through an integrated biopsychosocial models that bridge the gap between psychological stress and physiological dysfunction of the body. This narrative review synthesizes current research to unravel the mechanisms of underlying psychosomatic pain and its neurological implications. Epidemiological data highlight the widespread prevalence of these disorders globally, particularly in adolescents and high-risk adult populations, which are the ones with significant comorbidities like depression, anxiety, and chronic pain syndromes like fibromyalgia. The core of this paradigm shift lies in the emergence and integration of epigenetics, which demonstrates how chronic stress and trauma can induce stable, long-term changes in gene expression without altering the DNA sequence. Specifically, epigenetic modifications, such as DNA methylation of genes like FKBP5, NR3C1, and BDNF, are shown to dysregulate the hypothalamic-pituitary-adrenal (HPA) axis, heighten inflammatory responses, and impair neuroplasticity, thereby embedding psychological distress into a physical, somatic reality. ​Neurological investigations, particularly using functional neuroimaging, reveal that these disorders are not fabricated but are rooted in aberrant neural circuitry. Conditions like functional neurological disorder (FND) are characterized by disrupted connectivity between emotion-processing centers (e.g., the amygdala) and sensorimotor pathways, leading to involuntary physical symptoms. The clinical features of these disorders are multifaceted, marked by a heightened focus on bodily sensations, negative healthcare experiences, and significant functional impairment. Evolving beyond traditional methods, psychosomatic disorder treatment is now integrative and personalized. New approaches combine CBT with novel therapies like non-invasive brain stimulation, neurofeedback, and pharmacogenomics.